Iranian teachers’ and learners’ attitudes towards the use of e-portfolio in second language speaking assessment - Hossein Rezadoust Siah Khaleh Sar; Masoud Khalili Sabet; Amir Mahdavi Zafarghandi; Jaleh Hassaskhah (Language Testing in Asia)
Abstract This research explores Iranian teachers’ and students’ attitudes toward using e-portfolios for speaking assessment in an institutional context. This qualitative study involved 12 intermediate students as well as 14 EFL teachers at an English language institute (Safir) in Tehran, Iran. Data were gathered through interviews and focus group discussions. The study findings indicated that the majority of participants held a favorable opinion regarding the utilization of e-portfolios. The participants also identified a number of significant benefits of implementing e-portfolios, including raising students’ motivation and self-confidence, learning new information, successfully finishing English assignments, producing favorable learning outcomes, and improving students’ English ability. These results are assumed to shed light on the importance of considering e-portfolios by educational stakeholders to foster students’ excitement and involvement in learning.